Inclusive Education Implementation: the Experience of the Faculty of Primary Education - Dovzhenko, Tetiana (Educational Challenges, 2022)
Considering the current reality, there are new requirements for the organization of the educational process in higher education institutions of Ukraine. Thus, the problems and ways of the implementation of inclusive education for students with special educational needs are becoming increasingly important. The purpose of the study is to substantiate theoretically the problems and ways of implementing inclusive education in Ukraine based on the experience of the Faculty of Primary Education of H. S. Skovoroda Kharkiv National Pedagogical University. Methodology. A retrospective analysis of the development of inclusive higher education in Ukraine has been used; it has been found that it is necessary to organize an inclusive environment and implement training for students with special educational needs in higher education institutions. The study was based on the Convention on the Rights of Persons with Disabilities, Resolution of the Cabinet of Ministers of Ukraine of July 10, 2019 № 635 “On approval of the Procedure for the organization of inclusive education in higher education institutions”, educational programs on 013 Primary Education, and scientific and pedagogical works on conceptual approaches to the implementation of inclusive education; organization of training of persons with special educational needs; principles and functions of inclusive education, which indicated the need for inclusive education in higher education institutions. Results. The essence of the concept "inclusive education" has been defined. Problems of higher education of people with special needs have been described. The system of education of students with special needs has been determined. It is noted that art HUB for students and university teachers with special educational needs in H. S. Skovoroda Kharkiv National Pedagogical University has been opened. It has been determined that there are elective subjects “Fundamentals of inclusive education” (for the 3rd year students) and “Features of working with an inclusive child” (for the 4th year students) in the educational program “Primary Education” at the Faculty of Primary Education of H. S. Skovoroda Kharkiv National Pedagogical University. The educational program "Primary education with methods of special education" for applicants for the first (bachelor’s) level of higher education has been described. The examples of students’ working with an inclusive child are described. Conclusions. The process of successful integration of people with special needs in a higher education institution requires a systematic solution of many tasks. Creating an environment accessible to people with special needs is becoming an unconditional requirement for the development of higher education institutions and significantly affects the competitiveness of a modern IHE.